Efektivitas Pendekatan TPACK dalam Pembelajaran PAI untuk Meningkatkan Literasi Digital Siswa di SMK N 1 Pancung Soal - Eni Susrawati (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to evaluate the effectiveness of the TPACK (Technological Pedagogical and Content Knowledge) approach in Islamic Religious Education (PAI) learning to enhance students' digital literacy at SMKN 1 Pancung Soal. This approach integrates technology, pedagogy, and subject content to create an interactive and relevant learning experience in the digital era. Classroom Action Research (CAR) was employed, involving eleventh-grade students as research subjects. The findings indicate that the implementation of TPACK significantly improved students' digital literacy skills, including online information searching, source evaluation, and digital collaboration. Additionally, students demonstrated enhanced comprehension of religious materials and active participation in learning. The study recommends further development in teacher training for optimizing TPACK application in education. Keywords:,n, Digital Literacy, Technology-Based Learning, Classroom Action Research